Urgensi Kehujjahan Hadis dalam Pendidikan Islam dan Kurikulum Agama - Syarifah Aini Kamilah; Sri Bintang Abadi; Putri Salisatu Toyyiba; Eva Syarifatul Marifati Siti Maldani; Maslani Maslani (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2025)
This study discusses the importance of the authenticity of hadith in Islamic education and the integration of its values into the religious education curriculum. The focus is on the necessity of understanding the authenticity of hadith to ensure that the teachings are sound and relevant in shaping students' character. The research uses a qualitative approach with literature review to analyze the integration of hadith into the curriculum. The main findings show that applying hadith in the teaching of morals, discipline, and honesty has a positive impact on students' character, although there are challenges in selecting authentic hadith and addressing the lack of hadith knowledge among educators. The study emphasizes that mastering hadith knowledge and selecting relevant hadith are crucial in Islamic education.